Super-resolution of nodal and paranodal disruption in anti-pan-neurofascin-associated autoimmune nodopathy - da Cruz Neris Geßner, Vinicius; Linke, Janis Theobald; Peulen, Thomas-Otavio; Appeltshauser, Luise; Sommer, Claudia; Brämer, Dirk; Geis, Christian; Heinze, Katrin Gertrud; Doppler, Kathrin (Frontiers in Immunology, 2025)
IntroductionIn autoimmune nodopathies, autoantibodies target the nodes of Ranvier, impairing saltatory nerve conduction. Understanding the impact of autoantibody binding on protein assembly is crucial for gaining insights into the pathogenicity of different autoantibodies. We investigated nodal, paranodal, and cytoskeletal axonal proteins in teased fibers from a sural nerve biopsy of a patient with anti-pan-neurofascin autoantibodies. Conventional diagnostic tools, including fluorescence microscopy, often miss subtle alterations at the ultrastructural level.MethodsWe utilized direct stochastic optical reconstruction microscopy (dSTORM), a super-resolution fluorescence imaging technique, to assess the nanoscale architecture of nodal, paranodal, and cytoskeletal axonal proteins.ResultWhile conventional fluorescence microscopy revealed severe paranodal and nodal damage in 14% of the nodes, with 86% appearing normal at first glance, the super-resolved images revealed a decreased neurofascin-155 and Caspr-1 density, but preserved colocalization of these adhesion proteins in paranodes that initially seemed normal. At the nodes, sodium channel density and distribution remained intact, but neurofascin-186 density was reduced. Axonal beta-IV spectrin was altered only in severely damaged nodes. This indicates that axonal integrity is largely preserved, with a potentially reversible decrease in paranodal and nodal adhesion proteins in patients with nodopathy revealing subtle alterations in nodal integrity that are not apparent with conventional imaging.DiscussionThese likely reversible changes may explain the rapid recovery seen in patients with anti-pan-neurofascin autoantibodies following autoantibody depletion. Conversely, the small percentage of severely and axonally damaged nodes may account for the residual symptoms experienced by most patients.